A wear-resistant micro-nanostructure super-hydrophobic coating with photothermal effect and preparation method thereof
By spraying PDMS prepolymer and curing agent, combining micro and nano carbon black particles, an atmospheric coating with photothermal effect and wear resistance is solved, and the existing superhydrophobic surfaces are degraded after mechanical scratching or wear. Achieve efficient anti-icing effect.
Patent Information
- Application Number
- CN202311642423.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-04
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-12-04
AI Technical Summary
After mechanical scratches or wears, the superhydrophobic properties of the existing superhydrophobic surfaces are prone to decrease or fail, and lack light and thermal effects to achieve anti-icing effect.
Using a preparation method, by spraying PDMS prepolymer and curing agent, followed by spraying microcarbon black and nanocarbon black particle dispersion, the mass ratio of micronanocarbon black is controlled to form a coating with different micronano structures and photothermal effects. And at the end a layer of diluted PDMS prepolymer and curing agent mixture is added to enhance wear resistance.
It realizes a coating with superhydrophobic properties without the need for low-surface energy chemical modification, has strong photothermal effect and wear resistance, significantly improves the anti-icing effect, and is suitable for any material substrate.
Smart Images

Figure CN117447917B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of coating protection, and in particular to a wear-resistant micro-nanostructure super-hydrophobic coating with photothermal effect and a preparation method thereof. Background Art
[0002] The wettability of a solid surface is usually determined by the chemical composition and microstructure of the surface. Superhydrophobic surfaces have extremely important application prospects in defense, industrial production, and daily life due to their unique non-wettability (the contact angle between a water droplet and a solid surface is >150°, and the rolling angle is <10°). Inspired by the "lotus effect", the key to preparing superhydrophobic surfaces is to combine low surface energy materials with micron-nano hierarchical structures to construct micro-nano composite structures of bionic lotus leaf surfaces. Compared with a single micron or nanostructure, the micro-nano secondary hierarchical structure can effectively trap more air, form a stable air layer between the solid surface and the droplet, greatly reduce the solid-liquid contact area, and enable the surface to achieve a larger contact angle and a smaller rolling angle. This feature makes the micro-nanostructure superhydrophobic surface have good application prospects in the field of anti-icing. If the micro-nanostructure surface also has a strong photothermal effect, its anti-icing effect will be even better. Under the irradiation of sunlight, this surface can efficiently absorb sunlight and convert it into heat energy to heat the surface and achieve the effect of preventing ice or directly removing ice.
[0003] With the continuous development of micro-machining technology, various surface micro-nano structure preparation technologies have gradually matured. At present, the main methods for preparing bionic lotus leaf super-hydrophobic surfaces are dry / wet etching, laser ablation, chemical self-assembly, electrodeposition, template method, etc. These methods usually construct micro-nano rough structures first, and then modify them with low surface energy materials to achieve super-hydrophobicity. However, these methods usually have some challenges. One is that the prepared micro-nano structure is relatively fragile and easily affected by mechanical scratches or other external forces, resulting in a reduction in super-hydrophobic performance or even failure. In addition, the low surface energy coating is also susceptible to wear, exposing the hydrophilic material at the bottom, thereby weakening the super-hydrophobic performance. Therefore, the development of a micro-nano structure super-hydrophobic coating combining photothermal effect and wear resistance is of great significance for practical application needs. Summary of the invention
[0004] In view of this, the present invention provides a wear-resistant micro-nanostructure super-hydrophobic coating with photothermal effect and a preparation method thereof.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing a wear-resistant micro-nanostructure super-hydrophobic coating with photothermal effect comprises the following steps:
[0007] Step (1): Weigh a certain mass ratio of PDMS prepolymer and curing agent, stir them evenly, put them into a vacuum pump to remove bubbles, use a glue spreader to spin coat them onto a substrate, and then put them into an oven for pre-curing treatment to obtain a substrate coated with a certain PDMS thickness.
[0008] Step (2): adding a certain mass of micron carbon black particles and nano carbon black particles into an organic solvent for ultrasonic dispersion to obtain a uniform micron carbon black dispersion and a nano carbon black particle dispersion;
[0009] Step (3): Use a spray gun to first spray a micron carbon black dispersion on the surface obtained in step (1), and then spray a nano carbon black dispersion, and obtain a coating with different micro-nano structures and photothermal effects by controlling the mass ratio of micro-nano carbon black.
[0010] Step (4): spray a layer of PDMS prepolymer and curing agent mixture diluted with an organic solvent on the surface obtained in step (3), and cure at low temperature to enhance the wear resistance and mechanical stability of the coating.
[0011] Furthermore, in the step (1), the mass ratio of the PDMS prepolymer to the curing agent is 5:1 to 10:1; the vacuum degassing time is 30 min to 2 h; the speed of the glue spreader is 500 to 5000 r / min, and the spin coating time is 5 to 60 s; the oven curing temperature is 25 to 100 ° C, and the curing time is 5 min to 12 h; the substrate is any material such as metal, glass, silicon wafer or wood board.
[0012] Furthermore, in step (2), the particle size of the micron carbon black particles is 1 to 100 μm, and the particle size of the nano carbon black particles is 1 to 1000 nm; the organic solvent in step (2) and step (4) can be any one of n-hexane, anhydrous ethanol, acetone, chloroform, benzene, toluene, xylene, dichloromethane or ether.
[0013] Furthermore, in the step (3), the mass ratio of micron carbon black to nano carbon black is 1:0.01 to 0.01:1.
[0014] Furthermore, in the step (4), the concentration of the PDMS prepolymer and curing agent mixed solution diluted with an organic solvent is 0.01 to 0.1 g / mL; the curing temperature is 25 to 100° C., and the curing time is 5 min to 12 h.
[0015] Furthermore, the coating prepared by the above method has a strong photothermal effect, super hydrophobicity, wear resistance and durability, and is effective in photothermal deicing and anti-icing.
[0016] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0017] 1. The wear-resistant micro-nanostructure super-hydrophobic coating with photothermal effect of the present invention can have super-hydrophobic properties without modification of any low surface energy chemical substances.
[0018] 2. The wear-resistant micro-nanostructure super-hydrophobic coating with photothermal effect of the present invention can construct a wear-resistant micro-nanostructure with only a simple two-step spraying method, and maintain the integrity and super-hydrophobic properties of its micro-nanostructure under the action of external forces such as scratching and friction.
[0019] 3. The wear-resistant micro-nano structure super-hydrophobic coating with photothermal effect of the present invention has a strong photothermal effect, and the sprayed micro-nano particles can efficiently absorb sunlight and convert it into thermal energy, and has a strong application prospect in anti-icing.
[0020] 4. The wear-resistant micro-nanostructure super-hydrophobic coating with photothermal effect of the present invention has a simple preparation method, convenient operation, low energy consumption, low cost, green and environmental protection, is suitable for substrates of any material, and can be mass-produced industrially. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0022] Figure 1 These are scanning electron microscope images of the photothermal super-hydrophobic surface obtained at different magnifications when the mass ratio of micron carbon black to nanoparticles in Example 1 of the present invention is 1:0.01, and the contact angle of a water drop on the surface.
[0023] Figure 2 These are scanning electron microscope images of the photothermal super-hydrophobic surface obtained at different magnifications when the mass ratio of micron carbon black to nanoparticles in Example 2 of the present invention is 2:1, and the contact angle of a water drop on the surface.
[0024] Figure 3 These are scanning electron microscope images of the photothermal super-hydrophobic surface obtained at different magnifications when the mass ratio of micron carbon black to nanoparticles is 3:2 in Example 3 of the present invention, and the contact angle of a water droplet on the surface.
[0025] Figure 4 These are scanning electron microscope images of the photothermal super-hydrophobic surface obtained at different magnifications when the mass ratio of micron carbon black to nanoparticles in Example 4 of the present invention is 2:3, and the contact angle of a water drop on the surface.
[0026] Figure 5These are scanning electron microscope images of the photothermal super-hydrophobic surface obtained at different magnifications when the mass ratio of micron carbon black to nanoparticles in Example 5 of the present invention is 1:2, and the contact angle of a water droplet on the surface.
[0027] Figure 6 These are scanning electron microscope images of the photothermal super-hydrophobic surface obtained at different magnifications when the mass ratio of micron carbon black to nanoparticles in Example 6 of the present invention is 0.01:1, and the contact angle of a water droplet on the surface.
[0028] Figure 7 It is the light absorption spectrum of the photothermal superhydrophobic surface with different micro-nano mass ratios.
[0029] Figure 8 It is the average surface temperature of photothermal superhydrophobic surfaces with different micro-nano mass ratios under 1 times the intensity of sunlight.
[0030] Fig. 9 This is a graph showing the change in contact angle and rolling angle of the photothermal superhydrophobic surface with a micro-nano mass ratio of 3:2 as a function of wear distance.
[0031] Fig.10 This is a test chart of the hydrophobic performance of a photothermal super-hydrophobic surface with a micro-nano mass ratio of 3:2 after being mechanically scratched. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] A wear-resistant micro-nanostructure super-hydrophobic coating with photothermal effect and a preparation method thereof, comprising the following steps:
[0034] Step (1): Weigh a certain mass ratio of PDMS prepolymer and curing agent, stir them evenly, put them into a vacuum pump to remove bubbles, use a coating machine to spin coat them onto a substrate, and then put them into an oven for pre-curing treatment to obtain a substrate coated with a certain PDMS thickness.
[0035] Step (2): adding a certain mass of micron carbon black particles or nano carbon black particles having a photothermal effect into an organic solvent for ultrasonic dispersion to obtain a uniform micron carbon black or nano carbon black particle dispersion;
[0036] Step (3): Use a spray gun to first spray a micron carbon black dispersion on the surface obtained in step (1), and then spray a nano carbon black dispersion, and obtain a coating with different micro-nano structures and photothermal effects by controlling the mass ratio of micro-nano carbon black.
[0037] Step (4): spray a layer of PDMS prepolymer and curing agent mixture diluted with an organic solvent on the surface obtained in step (3), and cure at low temperature to enhance the wear resistance and mechanical stability of the coating.
[0038] Furthermore, in the step (1), the mass ratio of the PDMS prepolymer to the curing agent is 5:1 to 10:1; the vacuum degassing time is 30 min to 2 h; the speed of the glue spreader is 500 to 5000 r / min, and the spin coating time is 5 to 60 s; the oven curing temperature is 25 to 100 ° C, and the curing time is 5 min to 12 h; the substrate is any material such as metal, glass, silicon wafer or wood board.
[0039] Furthermore, in the step (2), the particle size of the micron carbon black particles is 1 to 100 μm, and the particle size of the nano carbon black particles is 1 to 1000 nm; the organic solvent can be any one of n-hexane, anhydrous ethanol, acetone, chloroform, benzene, toluene, xylene, dichloromethane or ether.
[0040] Furthermore, in the step (3), the mass ratio of micron carbon black to nano carbon black is 1:0.01 to 0.01:1.
[0041] Furthermore, in the step (4), the concentration of the PDMS prepolymer and curing agent mixed solution diluted with an organic solvent is 0.01 to 0.1 g / mL; the curing temperature is 25 to 100° C., and the curing time is 5 min to 12 h.
[0042] Furthermore, the coating obtained in step (4) has a strong photothermal effect, super hydrophobicity, wear resistance and durability, and is effective in photothermal deicing and anti-icing.
[0043] Example 1
[0044] Embodiment 1 of the present invention provides a wear-resistant micro-nanostructure super-hydrophobic coating with photothermal effect and a preparation method thereof, comprising the following steps:
[0045] (1) In this example, an aluminum metal plate was used as the substrate. 5 g of PDMS prepolymer and 0.5 g of curing agent were weighed at a mass ratio of 10:1. After being stirred evenly, the mixture was placed in a vacuum pump to remove air bubbles. The mixture was pre-coated on the aluminum substrate. A coating machine was used to spin coat the mixture at a speed of 2000 r / min for 10 seconds to obtain a layer of PDMS solution on the surface. The mixture was placed in an oven at 80°C for 12 minutes for pre-curing treatment to obtain a substrate coated with a certain PDMS thickness.
[0046] (2) 0.6 g of micron carbon black particles (particle size 10 μm) with photothermal effect and 0.06 g of nano carbon black particles (particle size 20 nm) with photothermal effect were added to 20 mL of n-hexane solution, and ultrasonically dispersed for 2 h to obtain a uniform dispersion. The micron carbon black dispersion was first sprayed on the surface obtained in step (1), and then the nano carbon black dispersion was sprayed to obtain a coating with a mass ratio of micron carbon black to nano carbon black of 1:0.01.
[0047] (3) Weigh 0.3 g of PDMS prepolymer and 0.03 g of PDMS curing agent into 10 mL of n-hexane, place on a magnetic stirrer and stir at room temperature for 30 min, spray the mixture onto the surface obtained in step (2) with a spray gun, and place in an 80° C. oven for 2 h of curing to form a coating surface with a micro-nano structure.
[0048] Example 2
[0049] Embodiment 2 of the present invention provides a wear-resistant micro-nanostructure super-hydrophobic coating with photothermal effect and a preparation method thereof. The preparation method is the same as that of Embodiment 1, except that the mass of the micron carbon black particles in step (2) is 0.6 g, and the mass of the nano carbon black particles is 0.3 g, and finally a coating with a mass ratio of micron carbon black to nano carbon black of 2:1 is obtained.
[0050] Example 3
[0051] Embodiment 3 of the present invention provides a wear-resistant micro-nanostructure super-hydrophobic coating with photothermal effect and a preparation method thereof. The preparation method is the same as that of Embodiment 1, except that the mass of the micron carbon black particles in step (2) is 0.6 g, and the mass of the nano carbon black particles is 0.4 g, and finally a coating with a mass ratio of micron carbon black to nano carbon black of 3:2 is obtained.
[0052] Example 4
[0053] Embodiment 4 of the present invention provides a wear-resistant micro-nanostructure super-hydrophobic coating with photothermal effect and a preparation method thereof. The preparation method is the same as that of Embodiment 1, except that the mass of the micron carbon black particles in step (2) is 0.4 g, and the mass of the nano carbon black particles is 0.6 g, and finally a coating with a mass ratio of micron carbon black to nano carbon black of 2:3 is obtained.
[0054] Example 5
[0055] Embodiment 5 of the present invention provides a wear-resistant micro-nanostructure super-hydrophobic coating with photothermal effect and a preparation method thereof. The preparation method is the same as that of Embodiment 1, except that the mass of the micron carbon black particles in step (2) is 0.3 g, and the mass of the nano carbon black particles is 0.6 g, and finally a coating with a mass ratio of micron carbon black to nano carbon black of 1:2 is obtained.
[0056] Example 6
[0057] Example 6 of the present invention provides a wear-resistant micro-nanostructure super-hydrophobic coating with photothermal effect and a preparation method thereof. The preparation method is the same as that of Example 1, with the only difference that in step (2), the mass of the micron carbon black particles is 0.06g, and the mass of the nano carbon black particles is 0.6g, and finally a coating with a mass ratio of micron carbon black to nano carbon black of 0.01:1 is obtained.
[0058] The surface morphology, wettability, photothermal properties and wear resistance of the coatings with micro-nano structures obtained in Examples 1 to 6 were characterized. Figure 1 It can be seen that when the mass ratio of micro-nano carbon black is 1:0.01, there are only sporadic micron particles distributed on the surface. With the addition of nano carbon black content, many nanoparticles are distributed on the surface on the basis of the original micron-level structure, forming a bionic lotus leaf "papillary" micro-nano structure ( Figure 2-Figure 5 ). When the mass ratio of micro-nano carbon black is 3:2, the micro-nano secondary hierarchical structure of the surface is more obvious. With the further increase of nano carbon black content, the surface does not show obvious micro-nano protrusion structure. The contact angle of all sample surfaces is greater than 150°, and the rolling angle is less than 5°, showing excellent superhydrophobicity.
[0059] Figure 7 It shows that surfaces with different micro-nano carbon black mass ratios can strongly absorb broad-spectrum sunlight in the ultraviolet, visible and near-infrared regions, and the light absorption rate in the wavelength range of 200nm to 2500nm is stable at ~98%, showing excellent light absorption performance. Figure 8 It shows that under 1 times the solar intensity, the average surface temperature of all samples continues to increase with time. Among them, the surface of the sample with a micro-nano carbon black mass ratio of 3:2 shows the highest photothermal conversion performance, and the temperature reaches 59.2°C at 15 minutes.
[0060] After rubbing the surface with a micro-nano carbon black mass ratio of 3:2 with sandpaper under the action of a 200g weight, it can be seen that after 200cm of wear, the surface still exhibits excellent superhydrophobicity, with a contact angle of 158° and a rolling angle of 5° ( Fig. 9 In addition, after using pointed tweezers to scrape the surface of the sample back and forth, its contact angle remained above 150°, and after immersing it in water and taking it out, the surface remained dry ( Fig.10 ).
[0061] The above experiments show that the micro-nanostructured super-hydrophobic coating obtained by the present invention has a strong photothermal effect, super-hydrophobicity, and wear resistance and durability.
[0062] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0063] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a wear-resistant micro-nanostructure super-hydrophobic coating with photothermal effect, characterized in that: The steps include: Step (1): weighing a certain mass ratio of PDMS prepolymer and curing agent, stirring evenly, vacuuming to remove bubbles, spin coating the prepolymer on a substrate using a coating machine, and then placing the prepolymer in an oven for pre-curing treatment to obtain a substrate coated with a certain PDMS thickness; Step (2): adding a certain mass of micron carbon black particles and nano carbon black particles having a photothermal effect into an organic solvent for ultrasonic dispersion to obtain a uniform micron carbon black dispersion and a nano carbon black particle dispersion; Step (3): using a spray gun to first spray a micron carbon black dispersion on the surface obtained in step (1), and then spray a nano carbon black dispersion, and obtain a coating with different micro-nano structures and photothermal effects by controlling the mass ratio of micro-nano carbon black; Step (4): spraying a layer of PDMS prepolymer and curing agent mixture diluted with an organic solvent on the surface obtained in step (3), and curing at low temperature to enhance the wear resistance and mechanical stability of the coating; In the step (1), the mass ratio of PDMS prepolymer to curing agent is 5:1 to 10:1; the vacuum degassing time is 30 min to 2 h; the speed of the glue machine is 500 to 5000 r / min, and the spin coating time is 5 to 60 s; the oven curing temperature is 25 to 100 ° C, and the curing time is 5 min to 12 h; the substrate is metal, glass, silicon wafer or wood board; In the step (2), the particle size of the micron carbon black particles is 1 to 100 μm, and the particle size of the nano carbon black particles is 1 to 1000 nm; In the step (3), the mass ratio of micron carbon black to nano carbon black is 1:0.01 to 0.01:1; The organic solvent in step (2) and step (4) is any one of anhydrous ethanol, acetone, chloroform, benzene, toluene, xylene, dichloromethane or ether.
2. The method according to claim 1, characterized in that In the step (4), the concentration of the PDMS prepolymer and curing agent mixed solution diluted by the organic solvent is 0.01-0.1 g / mL; the curing temperature is 25-100° C., and the curing time is 5 min-12 h.
3. A super-hydrophobic coating prepared by the method described in any one of claims 1-2, characterized in that, The coating has strong photothermal effect, super-hydrophobicity, wear resistance and durability, and is effective in photothermal deicing and anti-icing.
Citation Information
Patent Citations
Super-hydrophobic photo-thermal deicing coating as well as preparation method and application thereof
CN116535715A
Cited By
Preparation method of flexible anti-covering / deicing coated fabric
CN119711196A
A method of making a flexible anti-icing / icephobic coated fabric
CN119711196B